Morphological and molecular taxonomic analysis of Pseudopoda Jäger, 2000 (Araneae: Sparassidae: Heteropodinae) in Sichuan Province, China - Jäger, Peter; Li, Shuqiang; Krehenwinkel, Henrik (Zootaxa, 2015)
The genus Pseudopoda Jäger, 2000 is revised from material collected in Sichuan province. A molecular analysis shows the utility of DNA markers to support taxonomic hypotheses in Sparassidae. Two new species are described: Pseudopoda coenobium spec. nov. from Emeishan (male, female) and Pseudopoda wu spec. nov. from Lugu Lake at the border to Yunnan (male, female). The latter species exhibits a unique reduction of the conductor and a strongly developed embolus. The female of Pseudopoda virgata (Fox, 1936) is described for the first time, the male is redescribed, the known range of the geographical distribution is considerably extended to the East (Baoxing and Tienqiang County), the vertical distribution range is extended from 300 m to slightly more than 2000 m. The male of Pseudopoda signata Jäger, 2001 is described for the first time, the female is redescribed, the known distribution range of this species is extended from Muge Cuo Lake over Kangding town to the valleys of Paomashan, Gonggashan and Yanzi. It shows a strong morphological variation, which may be interpreted as developing subspecies status in different valleys. However, according to results from a molecular analysis it is clearly considered intraspecific variability. Three further species are recorded from Sichuan: Pseudopoda emei Zhang et al., 2013, Pseudopoda sp. cf. yunnanensis (Yang & Hu, 2001) and Pseudopoda rivicola Jäger and Vedel, 2007.